LINGKUNGAN TEKTONIK OFIOLIT KOMPLEK MELANGE CILETUH JAWA BARAT BERDASARKAN PENDEKATAN PETROLOGI - -, Aton Patonah (Bulletin of Scientific Contribution, 2011)
The ophiolite sequence of Ciletuh Melange Complex consist of serpentinite, serpentinized harzburgit, dunit, gabro and basalt. Part of the ophiolite partly has been metamorphismed, produce metamorphic rocks. The result of mineral chemical analisis which is supported by geochemical date, the rock shows that the similar character with Duaga Island – Witu Island, Papua Newguinea and Mariana Trench Island arc, that is Island Arc It is signed by the low of forsterite (80-82), there is the existence of magmatic impregnation process, the low Al content in pyroxen showed the increase of degree of partial melting which followed by the increase Si, Mg and Ca content, meanwhile Ti, Cr and Na content decrease followed by the increase degree of partial melting. The ophiolite rock which appear in complex mélange Ciletuh has closed relationship with tectonic setting process which happened in that area. Those approximately happened on Tersier age (Eosen- lower Oligosen), that is accretional is formed in complex mélange Ciletuh, subduction zone move to the west with the direction north-northwest – south-southeast by the appearance of litological, by the present of ultramafics rocks which tectonized and consist of serpentinite and pillow lavas and mixed with sedimen pond. As the same time, also is formed obduction so that result metamorphism process and became metamorphic rock.